Construction a comprehensive health training program for women in the first period of adulthood - Galyna Artemyeva; Iryna Latvynska (Kharkiv State Academy of Physical Culture, 2020)
Purpose: to determine the effectiveness of building a comprehensive program of health training for women of the first period of adulthood. Material and methods: the research lasted during the 2019-2020 academic year on the basis of the fitness club "Territory Fitness". According to the homogeneitic indicators, two groups of women of the first period of adulthood - control (CG) and experimental (EG) were formed, 13 people in each group. Modern research methods were used: theoretical analysis and synthesis of literary sources, pedagogical observation, pedagogical experiment, pedagogical testing, medical and biological methods, methods of mathematical statistics. Results: in the process of conducting an experimental study, the program of health training was constructed. The program took into account the distribution of physical load depending on the tasks of each period, stage, meso and microcycle. Conclusions: during the experiment, significant intergroup changes in the somatometric and functional indicators of women of the first period of adulthood were observe at p <0.05 and physical fitness at p <0.05, at p <0.01, at p <0.001. The increase in somatometric indicators and indicators of the functional state of the body of women EG is 4.7% - 17.3%. At the same time, in women with CG, the range of changes in these indicators ranges from 0.4% to 12.2%. In terms of physical preparedness, there is also a more significant their increase in women with EG, and the range is from 14% to 45.8%. In women with CG, the increase in physical preparedness is in the range of 7% - 24%.